Effective management of advanced colon cancer genotyping microsatellite stable/microsatellite instable-low with Kirsten rat sarcoma viral oncogene mutation using nivolumab plus ipilimumab combined with regorafenib and irinotecan: A case report. (June 2021) - Cui, Yingqiang; Ou, Yimeng; Luo, Yongping; Yu, Jiongbiao; Lin, Yiguang; Chen, Size
Microsatellite stable /microsatellite instable-low is the most common colorectal cancer genotype, counting for approximately 85% of common colorectal cancer patients. Treatment of advanced microsatellite stable/microsatellite instable-low colorectal cancer is difficult and successful pharmacological treatment options are currently lacking. Here, we report a case of a 37-year-old man with advanced colorectal cancer genotyping microsatellite stable/microsatellite instable-low with a Kirsten rat sarcoma viral oncogene (G12V) mutation. Following palliative surgery, the patient did not response to the common recommended chemotherapy FOLFIRI regimen and other chemotherapy options. Finally, the patient was successfully treated using a unique combinational immunotherapy, using nivolumab plus ipilimumab combined with regorafenib and irinotecan. Significant improvement in the Karnofsky Performance Status scores, liver function and well-being, reduction in serum tumor biomarkers, and reduction in the size of multiple liver metastatic tumors was evident. This report provides a rare case in which a unique and effective combinational immunotherapy for refractory advanced colon cancer patients is discussed. It encourages further research into combined immunotherapy for immuno-insensitive colon cancer patients.